Headache in long COVID as disabling condition: A clinical approach - Rodrigues, Arthur Nascimento; Dias, Apio Ricardo Nazareth; Paranhos, Alna Carolina Mendes; Silva, Camilla Costa; Bastos, Thalita da Rocha; Brito, Bárbara Barros de; da Silva, Nívia Monteiro; de Sousa, Emanuel de Jesus Soares; Quaresma, Juarez Antônio Simões; Falcão, Luiz Fábio Magno (Frontiers in Neurology, 2023)
Background and Purpose: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can exacerbate previous headaches problems or change the type of pain experienced from headaches. This study aimed to investigate the clinical features of Long COVID headaches. Method: This is a cross-sectional, descriptive, and analytical observational study including 102 patients (with previous headache, n = 50; without previous headache, n = 52) with Long COVID and headache complaints. The Migraine Disability Assessment Test and Visual Analog Pain Scale were used to collect data on their headaches, and a standardized protocol. Results: The patients in this study who reported having headaches before COVID-19 had a longer duration of headache in the Long COVID phase than that in the pre-long COVID phase (p = 0.031), exhibited partial improvement in headache symptoms with analgesics (p = 0.045) and had a duration of Long COVID of less than 1 year (p = 0.030). Patients with a moderate or severe disability and those classified as having severe headaches in the Long COVID phase and these headaches exhibited a tendency to become chronic. Hospital admission (odds ratio [OR] = 3.0082; 95% confidence interval [CI]: 1.10–8.26), back pain (OR = 4.0017; 95% CI: 1.13–14.17), insomnia (OR = 3.1339; 95% CI: 1.39–7.06), and paraesthesia (OR = 2.7600; 95% CI: 1.20–6.33) were associated with headache in these patients. Conclusion: Headache is a disabling condition for patients with Long COVID and it seems to exacerbate the condition of those with headaches prior to contracting COVID-19.